High CD36 expression in the tumor microenvironmental vasculature correlates with unfavorable overall survival in high grade serous ovarian cancer - Christina T. Grech; Stefanie Aust; Gerda Hofstetter; Esther Uhl; Lorenz Hinterleitner; Christoph Grimm; Stephan Polterauer; Dietmar Pils (Scientific Reports)
Abstract The scavenger receptor CD36 has gained increasing interest in cancer research, with various functions in cell metabolism, angiogenesis, and immune response. This study aimed to investigate the molecular role of CD36 expression on tumor vasculature of advanced high-grade serous ovarian cancer (HGSOC) tissues and its prognostic implication. Immunohistochemical staining for CD36 was performed on whole tissue slides of 109 patients with advanced HGSOC. Patients were divided into two groups based on CD36 expression, i.e. positive versus negative, and correlated to clinicopathologic and survival data. RNA sequencing, metabolomics, and proteomics data were correlated to the CD36 expression within a subpopulation. CD36 expression in tumor vasculature was significantly associated with unfavorable overall survival (OS), both in univariate (HR 1.71, p = 0.039) and multiple Cox regression analyses (HR 1.91, p = 0.021), considering age, FIGO stage, postoperative residual tumor, and bevacizumab treatment as covariates. Positive CD36 expression was significantly associated with postoperative residual tumor, reflecting high tumor-burden. (p = 0.042). RNA sequencing from isolated tumor cells revealed an activated ‘regulation of lipolysis in adipocytes’ pathway significantly associated with CD36 expression. Co-association gene expression network analysis revealed increased ribosomal activity and protein translation in tumor cells of CD36-positive samples. Proteomics analysis of ascites showed three overexpressed proteins involved in lipid metabolism (LCN2, CFHR1, and CFHR4) out of 21 significantly deregulated proteins. Metabolomic analyses of serum showed a significant decrease of 60 glycerophospholipids (mainly unsaturated ones) and eight amino acids, four essential proteinogenic, in patients with CD36 positive vessels. CD36 intratumoral vessel expression was associated with unfavorable OS in patients with advanced HGSOC. Our analyses support the role of CD36 in tumor metabolism, possibly via CD36+-endothelial cell-mediated glycerophospholipid/oxLDL uptake. Signs of increased tumor metabolism were found, as well as a decrease of specific metabolic building blocks, indicating a higher—presumably CD36–mediated—uptake capacity.